2021
DOI: 10.1080/1744666x.2021.1945442
|View full text |Cite
|
Sign up to set email alerts
|

Improving prediction of disease outcome for inflammatory bowel disease: progress through systems medicine

Abstract: Introduction: Inflammatory bowel diseases (IBDs) are lifelong conditions causing relapsing inflammation of the intestine. In the absence of a cure, clinical management of IBDs is extremely challenging since they present with a wide range of phenotypes and disease behaviors. Hence, there is an urgent need for markers that could guide physicians in making the right choice of the rapidly growing treatment options toward a personalized care that could improve the overall outcome. Areas covered: In this review, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…In the future, we may be able to select a subgroup of paediatric patients eligible for discontinuation of their biologic treatment, which may decrease use, as is currently studied in the BIOCYCLE study in adults with CD. 8 In conclusion, Burgess et al showed that use of biologics is rapidly increasing. Therefore, it is even more important to acknowledge the impact on patients, healthcare professionals and costs, and carefully weigh these factors against the benefits of use of biologics.…”
Section: N V I T E D E D I T O R I a L Editorial: Implications And Fu...mentioning
confidence: 98%
See 1 more Smart Citation
“…In the future, we may be able to select a subgroup of paediatric patients eligible for discontinuation of their biologic treatment, which may decrease use, as is currently studied in the BIOCYCLE study in adults with CD. 8 In conclusion, Burgess et al showed that use of biologics is rapidly increasing. Therefore, it is even more important to acknowledge the impact on patients, healthcare professionals and costs, and carefully weigh these factors against the benefits of use of biologics.…”
Section: N V I T E D E D I T O R I a L Editorial: Implications And Fu...mentioning
confidence: 98%
“…So far, biologic treatment started in children is generally continued until transfer to adult care. In the future, we may be able to select a subgroup of paediatric patients eligible for discontinuation of their biologic treatment, which may decrease use, as is currently studied in the BIOCYCLE study in adults with CD 8 …”
mentioning
confidence: 99%
“…Studies were excluded if met any of the following criteria: (1) did not refer to human studies; (2) did not refer to IBD; (3) were reviews, book chapters, guidelines, editorials, case reports, or comments; (4) had full text in languages other than English, Spanish, or Portuguese; (5) did not refer to neutrophil-related biomarkers (this criterion excludes compounds that act on neutrophils and/or influence their activity, but which are not expressed or secreted by them, such as antineutrophil cytoplasmic antibodies, and ratios like the neutrophil-to-lymphocyte ratio); (6) refer to tissues other than serum, plasma, or whole blood; and (7) refer to bloodbased neutrophil-related biomarkers not studied in relation to disease progression or treatment outcomes [e.g. only (differential) diagnosis] or unable to assess predictive ability due to lack of temporal relationships (e.g.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Identification of reliable predictors of treatment outcomes would foster the effective management of IBD. [3][4][5] Neutrophils are key players in the pathophysiology of IBD, and neutrophil infiltration in the gut correlates with disease activity in both UC and CD. 6 Part of the innate immune response, they produce reactive oxygen species, proteases, and proinflammatory cytokines that combat the microbial pathogens, but also damage the epithelial barrier and recruit more inflammatory cells, perpetuating the gut inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation